Utilization of the Cultural Heritage Site of the Raja Pauh Ranap Mosque as a Learning Medium to Grow Historical Awareness of MA Hismar Students, Indragiri Hulu Regency: Pemanfaatan Situs Cagar Budaya Masjid Raja Pauh Ranap Sebagai Media Pembelajaran Untuk Menumbuhkan Kesadaran Sejarah Siswa MA Hismar Kabupaten Indragiri Hulu - Dwi Retno Utami; Ahmal; Yanuar Al Fiqri (Santhet: (Jurnal Sejarah, Pendidikan Dan Humaniora), 2025)
This study explores the use of the Raja Pauh Ranap Mosque cultural heritage site as an educational medium to foster historical awareness among students at Madrasah Aliyah (MA) Hismar in Indragiri Hulu Regency, Indonesia. The background of the research stems from the limited integration of local historical resources into the history curriculum, which often relies heavily on textbook-based and lecture-centered approaches. The aim of this research is to describe the implementation of site-based learning using the mosque, analyze students’ historical awareness, and identify the challenges faced by teachers in this process. Employing a qualitative descriptive approach, data were collected through interviews, observations, and documentation involving teachers, students, school administrators, and community figures. The findings indicate that utilizing the heritage site as a learning medium significantly increased students’ motivation and engagement in history learning. Students demonstrated stronger historical consciousness, not only in understanding local history but also in developing appreciation and responsibility for cultural preservation. Moreover, the study found that the spiritual atmosphere of the mosque, combined with experiential learning activities, enriched the affective and reflective dimensions of historical learning. This research contributes a practical model of heritage-based learning that can be replicated in other educational settings, especially in regions with valuable cultural assets.